Music in Mississippi Secondary Schools, Grades 7-12 - Mississippi State Dept. of Education, Jackson. Div. of Instruction; Mississippi State Dept. of Education, Jackson. Div. of Instruction ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
A list and short description of types of spaces and other considerations for the design of an adequate music facility is provided. All personnel involved in the music programming should be considered. A bibliography and floor plans are included. (JS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Acoustical Environment; Building Design; Educational Facilities; Equipment; Guidelines; Music Education; Music Facilities; School Buildings